The catalytic effects of UiO-66 on enhancing hydrogen storage performance of MgH2 - Siti Nurqurratulainie, Miskan; Abdulkadir, Bashir Abubakar; Mohammad Ismail, -; Herma Dina, Setiabudi (Elsevier Ltd, 2025)
This study demonstrates the improved hydrogen storage performance of magnesium hydride (MgH2) through the incorporation of a zirconium-based metal-organic framework (MOF), UiO-66. The addition of UiO-66 significantly enhances the sorption kinetics and reduces the decomposition temperature to below 400 °C. Synthesized via a solvothermal route and stabilized by post-calcination at 300 °C, UiO-66 exhibits excellent thermal and chemical stability, making it a promising additive for hydrogen storage systems. The MgH2/UiO-66 composite shows an initial dehydrogenation temperature of 262 °C, which is 80 °C lower than that of milled MgH2. The apparent activation energy is reduced to 85.5 ± 5.5 kJ/mol, approximately 45 % of the pristine MgH2, indicating a significantly enhanced reaction pathway. At 250 °C, the composite achieves a hydrogen capacity of approximately 6.8 wt% within 3600 s and maintains stable performance over ten consecutive cycles. Particle size analysis via scanning electron microscopy (SEM) reveals finer dispersion and reduced agglomeration in the composite compared to milled MgH2 alone. The MgH2/UiO-66 system effectively functions as a “hydrogen pump,” facilitating faster hydrogenation/dehydrogenation kinetics and improved cycling stability. Hence, this study offers fresh insights to expand research and accelerate the advancement of hydrogen energy.